Analisis Hukum Islam Tentang Perlindungan Hukum Terhadap Konsumen Menurut Undang-Undang No. 8 Tahun 1999 - Akta Kurniawan; Nurul Kahotimah (LPPM Institut Al-Ma'arif Way Kanan, 2021)
ABSTRACT Consumer protection is a form of the efforts made to protect the right of producers and consumers in economic activity and minimize the occurrence of the resulting in losses for both parties whether it is producers and consumers.This research dilator overwhelmed with as the technology and the number of the form of efforts by the manufacturer to gain an advantage and the diverse needs onsumen in fulfilling the needs of human daily. It is indirectly put the position of consumers get more frail and prone to being the object the profiteers without regard to things that could have hurt consumers. With this, islam as a religion that has been set up several provisions in a couple of righteousness and the word of the messenger for profit with principles of justice and there is no trick. unsureWhile the indonesian government also do something similar to give a legal certainty and ensure safety for consumers in the law no. 8 years 1999 hereinafter referred to uupk formed on the date 20 april 1999 Islamic law and a legal instrument UUPK are two interlocking especially in law enforcement to consumer, well as, principles and objectives rights and obligations, consumers things are forbidden to be done by business players to run a business, as well as for, default clause islamic law and UUPK had the same viewpoint, is to remain ahead of ethics and forbid something is a trick that could potentially hurt consumer. In addition UUPK and Islamic law and also ensures equal rights between the producer and consumer gain and benefits. So lameness occurring to the position for this is those who can be removed